Pengembangan Media Pembelajaran Interaktif Berbasis Aplikasi Canva pada Materi Rantai Makanan Kelas V SD Negeri 02 Indralaya Utara - Muhammad Redho Romli Argo; Laihat; Esti Susiloningsih (EduInovasi: Journal of Basic Educational Studies, 2025)
Development of interactive learning based on the Canva application for food chain material for grade V of SD Negeri 02 Indralaya Utara. This study aims to develop interactive learning media that can increase students' interest and understanding of food chain material. The method used is the ADDIE development model. This method aims to develop interactive learning media for food chain material to obtain the level of validity and practicality of the developed learning media. The results of the material validity with a percentage of 94.44% which is very valid and the media validity of 89.47% with very valid criteria. The results of the analysis show that learning in grade V tends to be monotonous and less interactive, so interesting and varied media are needed. The learning media developed uses the Canva application, which offers various graphic design features to create interesting and easily accessible content. The trial of this media involved 20 students and showed very positive results, with a percentage of 95% of the student response questionnaire with very practical criteria and 100% of the teacher response questionnaire with a very valid category. The data from the trial results indicate that the interactive learning media based on the Canva application that was developed can be applied in learning at school.